Momentaufnahme : Junge Kunst aus Moskau. - Schrepffer, Anna; Altes Stadtmuseum, Münster; Stapelhaus Frankenwerft, Köln; Ravensberger Spinnerei, Bielefeld (Münster : Stadt Münster, 1989)
Gundlach, Sven ; Swesdotschotow, Konstantin ; Albert, Jurij ; Zakharov, Vadim ; Reuter, Andrej ; Filippow, Andrej ; Kopystjanskij, Igor ; Mironenko, Sergej ; Mironenko, Sergej ; Mironenko, Wladimir
Momentaufnahme : Junge Kunst aus Moskau, Altes Stadtmuseum, Münster, 12. Februar - 2. April 1989 ; Stapelhaus Frankenwerft, Köln, 21. Juni - 18. Juli 1989 ; Ravensberger Spinnerei, Bielefeld, 9. Oktober - 19. November 1989
boek
Keywords: Moskou